(untitled) (Research, Society and Development, 2021)
Introduction: The clinical pharmacist works to promote health, preventing adverse events and intervening in prescriptions to obtain positive clinical results. Continuously pharmacotherapeutic monitoring is able to reduce errors related to medications, thereby increasing the effectiveness and minimizing the risks of pharmacotherapy in this sense, this article aims to identify bibliographic productions on the attributions of the pharmacist in promoting patient safety in the context. Method: This is an integrative literature review based on bibliographic research. The search strategies allowed the identification of 571 articles in the selected databases. Throughout the analysis of titles and abstract, applying the inclusion criteria, 561 articles were excluded. In total, 10 articles were selected for analysis of the full text that participated in the review on the subject. Using criteria for inclusion and exclusion of articles, after reading and applying the selected criteria, 10 articles were selected for meeting all requirements. Results and discussion: The results highlight that the clinical pharmacist brings benefits through the identification of potential adverse events related to drug therapy and, consequently, contributes to patient safety in the positive outcome of the patient. Despite the well-established importance of the clinical pharmacist, the authors report that experiences have been discreetly reported and the importance of these services for children, adolescents and adults has led to interesting results. Final considerations: All studies demonstrate that the presence of the pharmacist exerts a beneficial interference to medical prescriptions, thus improving the quality of services provided to the patient, reducing deaths, the number and time of hospitalizations and reducing hospital costs.